Pengaruh Penghargaan Finansial, Pengetahuan Persyaratan Akuntan Publik Dan Lingkungan Keluarga Terhadap Minat Mahasiswa Akuntansi Dalam Pemilihan Karir Sebagai Akuntan Publik - Ni Kadek Ade Riski Sapitri; Cokorda Gde Bayu Putra; Ni Putu Yeni Yuliantari (UNHI Press, 2023)
Public accountants play a crucial part in society's decision-making processes. However, the number of accounting graduates in Indonesia is significantly lower than the number of practicing accountants. This suggests that public accounting is not yet a popular career choice amongst students. This research set out to answer the question,